Establishment Size Dynamics in the Aggregate Economy - Rossi-Hansberg, Esteban; Wright, Mark L. J (American Economic Review, 2007)
This paper presents a theory of establishment size dynamics based on the accumulation of industry-specific human capital that simultaneously rationalizes the economy-wide facts on establishment growth rates, exit rates, and size distributions. The theory predicts that establishment growth and net exit rates should decline faster with size, and that the establishment size distribution should have thinner tails, in sectors that use specific human capital less intensively. We establish that there is substantial cross-sector heterogeneity in US establishment size dynamics and distributions, which is well explained by relative factor intensities. (JEL L11, L16, L25).